Analisis Ketersediaan dan Kebutuhan Sumber Daya Air di Kecamatan Mamasa Kabupaten Mamasa - Nurfatimah, Nurfatimah (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
The availability of water in Indonesia, especially clean water, is still difficult to reach in some areas. The main problem of water resources in Indonesia is the availability of clean water from time to time becomes an unsolved problem. Residents who are dominated by the middle and lower economic circles, are forced to make choices in meeting their clean water needs. In addition, the problem of water resources in Indonesia still relies on flood and drought relief. The availability of water in Mamasa sub-district, especially clean water, is still a problem in the region. The increasing population in Mamasa District is one of the factors causing the increasing need for water. As it is known that Mamasa Subdistrict is the Capital of Mamasa Regency which has an area of ​​25,065 where the land area affects the availability of water in Mamasa Subdistrict. As the population increases in Mamasa District, it can cause the depletion of clean water in the region. Therefore, it is necessary to know the Water Carrying Capacity (DDA), Run Off, and the Maximum Capacity Value according to the Type of Land Use in order to know the quality and quantity of water availability in Mamasa District.